I11 21 years of surveillance for vitamin k deficiency bleeding in infants: policy changes in australia and international comparisons. (12th March 2018) - Zurynski, YA; Ridley, G; Jalaludin, B; Elliott, E; ,
Abstract : Background: The NHMRC recommends Vitamin K at birth for the prevention of Vitamin K Deficiency Bleeding (VKDB). Intramuscular injection (IMI) is the preferred route of administration but oral dosing may be chosen. We describe the incidence and outcome of VKDB during changes in vitamin K prophylaxis policy and the introduction of a new formulation of Vitamin K. Methods: Infants with VKDB were identified by active surveillance through the Australian Paediatric Surveillance Unit (APSU), 1993–2012. Demographics, clinical characteristics and outcomes were collected via questionnaire completed by the reporting doctor. Results: Fifty-one cases of VKDB were reported; 36 late onset and 15 early/classical. Twenty-seven (53%) infants received no vitamin K, in 22 (81%) of these parents refused consent, and this was the case in 92% of the 12 home births. The national incidence of VKDB was 0.9/100, 000 live births per annum. Higher incidence was detected in 1993 (4.6/100, 000) when oral dosing was recommended and in 2000 (2.3/100, 000) coinciding with changes in Vitamin K formulation to enable oral dosing. Of 7 infants who received oral doses of Vitamin K, only 1 received the complete course of 3 doses. Surprisingly, 6 cases of VKDB were reported in 2013 (2/100, 000); parents refused consent in 5. Thirty-one (61%) infants had a good outcome after bleeding was corrected with vitamin K. Ongoing morbidity was almost exclusively confined to those with late onset VKDB (12/36, 30%) and related to underlying liver disease, or intracranial haemorrhage. Six (12%) infants died including one in 2013 due to intracranial haemorrhage. Adverse outcomes have also been reported in New Zealand and in the United Kingdom among predominantly breast-fed infants whose parents refuse Vitamin K. Conclusion: IMI injection remains the most reliable and recommended mode of administering vitamin K to newborns, however, some parents refuse to consent to Vitamin K prophylaxis, even in recent years. A broad awareness and education campaign is needed to prevent infant deaths due to VKDB.